Doing Complex Reform Through PDIA: Judicial Sector Change in Mozambique. (8th December 2015) - Andrews, Matt
Summary: Many public sector reforms change governmental forms without improving functionality. Recent work suggests this is because countries adopt mechanisms that do not fit their contexts, without an effective adaptation strategy. The work posits that reforms could be more effective if they were introduced through more adaptive processes, like problem‐driven iterative adaptation (PDIA). This approach has deep roots in various literatures but many observers still ask how it actually works in practice. This paper responds to such question by describing an action research study where PDIA was used to facilitate process reform in Mozambique's judicial sector. It shows how the approach (i) revealed contextual factors that often limit reform success and (ii) fostered adaptive progress around these factors, towards a functional solution. Copyright © 2015 John Wiley & Sons, Ltd.